2010
DOI: 10.3201/eid1607.100070
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsia felis–associated Uneruptive Fever, Senegal

Abstract: During November 2008–July 2009, we investigated the origin of unknown fever in Senegalese patients with a negative malaria test result, focusing on potential rickettsial infection. Using molecular tools, we found evidence for Rickettsia felis–associated illness in the initial days of infection in febrile Senegalese patients without malaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
126
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(135 citation statements)
references
References 14 publications
(27 reference statements)
6
126
2
1
Order By: Relevance
“…The most intriguing feature of our studies was the identification of Rickettsia felis as a causative agent of common febrile disease in rural Senegal. 3,4 Among febrile patients, the overall reported incidence of illness caused by R. felis was approximately 2-4%, and similar results have been independently reported for Kenya. 5,6 Moreover, tick-borne Rickettsia species (R. conorii, R. africae, R. massiliae, R. aeschlimannii, and R. sibirica mongolitimonae) were identified in vectors and patients in Senegal, where seroprevalence against spotted fever group rickettsiae in the healthy population may reach 51%.…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…The most intriguing feature of our studies was the identification of Rickettsia felis as a causative agent of common febrile disease in rural Senegal. 3,4 Among febrile patients, the overall reported incidence of illness caused by R. felis was approximately 2-4%, and similar results have been independently reported for Kenya. 5,6 Moreover, tick-borne Rickettsia species (R. conorii, R. africae, R. massiliae, R. aeschlimannii, and R. sibirica mongolitimonae) were identified in vectors and patients in Senegal, where seroprevalence against spotted fever group rickettsiae in the healthy population may reach 51%.…”
Section: Introductionsupporting
confidence: 69%
“…These works identified a novel healthcare problem in Africa: acute R. felis-induced fever that mimics malaria. 3,6 Evidently, this acute fever may be responsible for a significant proportion of the non-malarial fevers in Africa. However, the epidemiology and clinical picture of this acute R. felis fever remain to be characterized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory studies have indicated that both Rickettsia species are maintained in fleas by vertical and horizontal transmission and can persist for life without causing damage. 11 Rickettsia felis is transmitted to humans by flea bites and contact with flea feces. Recently, R. felis was detected in patients with fever of unknown cause, with a prevalence of 4.4% in Senegal 11 and 3.7-7.2% in Kenya.…”
Section: Introductionmentioning
confidence: 99%
“…En Latinoamérica y el Caribe, actualmente se destaca como la especie reportada en el mayor número de países (9). Es evidente, entonces, que R. felis está emergiendo y es importante en la etiología del síndrome febril agudo (10)(11)(12).…”
unclassified